Detection of Flood Hazard in Urban Areas Using GIS: Izmir Case. (2016) - Ozkan, Sevim Pelin; Tarhan, Cigdem
Abstract: The aim of this study is to predict the potential flood-hazard areas using Shuttle Radar Topography Mission - Digital Elevation Model (SRTM-DEM). The study area is the province of Izmir. SRTM-DEM of the Izmir Province has 90 m of grid size resolution; 45 m of horizontal accuracy; and 15 m of vertical accuracy. Within this study, obtaining spatial information on flood-hazard by using Izmir digital terrain models and by 3D analysis that will help to achieve the regional flood hazard management scheme is aimed. Flood-hazard areas have been identified by the use of digital elevation model covering the study area. The main rivers in the study area are Gediz, Kucuk Menderes and Bakircay that creates the coastal flood plains. In order to estimate the spatial distribution of flood-hazard areas in İzmir, five factors are used: flow accumulation, land use, slope, rainfall intensity, and elevation. The classic hydrological modelling approach was applied to determine the rainfall intensity; rainfall intensity of study region is created with the average amount of total rainfall intensity of fifteen stations in the two basins per minute using the interpolation method (spline interpolation). By the digitizing rivers, topography, flow direction and flow accumulation, as well as the flood detention areas are determined. These factors were combined with the weighted overlay method to determine categorized flood-hazard areas. As a result, possible flood-hazard areas have been determined in the case of Izmir Province.